Praktik Jurnalisme Robot Sebagai Akhir Profesi Jurnalis - Utoyo, Arsa Widitiarsa; Putranto, Algooth (Magister of Communication Science, Sahid University Jakarta., 2022)
Major media corporations in the West have begun to use AI (Artificial Intelligence) to write news. In Indonesia, news site Beritagar.id is the first to use AI to write news. Is